Constraints on the thermal evolution of metamorphic core complexes from the timing of high-pressure metamorphism on Naxos, Greece - Lamont, TN; Smye, AJ; Roberts, NMW; Searle, MP; Waters, DJ; White, RW (Geological Society of America, 2023)
Metamorphic core complexes are classically interpreted to have formed during crustal extension, although many also occur in compressional environments. New U–(Th)–Pb allanite and xenotime geochronologic data from the structurally highest Zas Unit (Cycladic Blueschist Unit) of the Naxos metamorphic core complex, Greece, integrated with pressure–temperature–time (P–T–t) histories, are incorporated into a thermal model to test the role of crustal thickening and extension in forming metamorphic core complexes. Metamorphism on Naxos is diachronous, with peak metamorphic conditions propagating down structural section over a ~30–35 m.y. period, from ca. 50 Ma to 15 Ma. At the highest structural level, the Zas Unit records blueschist-facies metamorphism (~14.5–19 kbar, 470–570 °C) at ca. 50 Ma, during northeast-directed subduction of the Adriatic continental margin. The Zas Unit was subsequently extruded toward the SW and thrust over more proximal continental margin and basement rocks (Koronos and Core units). This contractional episode resulted in crustal thickening and Barrovian metamorphism from ca. 40 Ma and reached peak kyanite-sillimanite–grade conditions of ~10–5 kbar and 600–730 °C at 20–15 Ma. Model P–T–t paths, assuming conductive relaxation of isotherms following overthrusting, are consistent with the clockwise P–T–t evolution. In contrast, extension results in exhumation and cooling of the crust, which is inconsistent with key components of the thermal evolution. Barrovian metamorphism on Naxos is therefore interpreted to have resulted from crustal thickening over a ~30–35 m.y. time period prior to extension, normal faulting, and rapid exhumation after a thermal climax at ca. 15 Ma.